Pedagogical Principles Of Developing A Healthy Lifestyle And Motivation In Youth (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In the article, the pedagogical foundations of the formation of a healthy lifestyle and the development of motivation in students and young people and the opinions of various scientists related to the motivation of young people are widely covered. Detailed information on the main forms and sources of the correct formation of a healthy lifestyle is provided.